THE ROLE OF TEACHER’S CULTURAL EXPOSURE ON INDONESIAN EFL LEARNERS’ INTERCULTURAL SENSITIVITY - Siregar, Fenty Linda (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
A number of researchers argue that attaining intercultural communicative competence (ICC) should become the goal of every EFL and ESL learners (Bryam, 1997, and Alptekin, 2002). Shin (2010) states that helping the learners to develop their intercultural sensitivity (IS) can be a starting point for improving their ICC in English. Besides, teachers’ cultural exposure might play an important role to develop learners’ IS. Therefore, this study aims at investigating the role of teachers’ cultural exposures on intercultural sensitivity of EFL students. The participants of the study are 160 Indonesian EFL learners who are studying English at either English department or D3 English programme at Maranatha Christian University. In order to gather data needed, the present study employed a semi-structured interview and a questionnaire containing 12 questions about teacher’s cultural exposures and 24 questions taken from the Intercultural Sensitivity Scale (ISS) which was formulated by G. M. Chen and Starosta (2000). Descriptive statistics (means and standard deviations) and a Pearson Product-Moment Correlation analysis were used to answer the questions raised in the study. The findings of the study revealed that the participants had a moderate intercultural sensitivity level and received more exposures of native English speakers’ cultures than exposures of non- native English speaker’s and Indonesian cultures from their teachers. There was also no correlation found between the intercultural sensitivity level of the participants and teachers’ cultural exposures. The positive correlation was only shown in the correlation between teachers’ cultural exposures and a variable of IS which is participants’ interaction engagement.Keywords: Intercultural, Sensitivity, Cultural, Exposures